Vitamina T : your daily dose of tacos, tortas, tamales, and more Mexican street food classics - Gaviria, Jorge; Nuñez, Fermín; Ben Amotz, Allegra (Clarkson Potter/Publishers, 2026)
"Discover over 100 delicious takes on classic Mexican street foods. You're guaranteed to get your daily dose of vitamin T--the unofficial Mexican food group that celebrates tacos, tortas, tamales, and more. Celebrated chef Fermín Núñez and masa-purveyor-to-the-stars Jorge Gaviria take us on a journey through the sizzling streets of Mexico and Mexican communities in the U.S. to show us how we can capture some of the magic of this cuisine in our home kitchens. These street foods (tacos, tostadas, tamales, and other vitamin T favorites) represent the culinary experiences across Mexican foodways. Explore the beautiful sights and bold flavors of a late-night taqueria, a charcoal-burning clay comal teeming with hoja-santa-wrapped tetelas, and all of the tamales at all of the times. This book features mouthwatering Mexican staples as well as contemporary twists. These dishes are emblematic of what makes Mexico a culinary cornerstone, and Vitamina T translates them into approachable, easy to prepare recipes for home cooks. Through traditional techniques, practices developed by Fermín and Jorge, with dishes for any meal, drinks, salsas, and more, this book has everything you need to bring a late night Mexico City street food crawl into your own home"-- Provided by publisher.